Evaluation of high temperature performance of SBS + Gilsonite modified binder - Kök, Baha Vural; Yılmaz, Mehmet; Güler, Murat (My University, 2011)
SBS is a widely used polymer modi?er for asphalt binders to improve the performance properties of hot mix asphalt. SBS is nearly indispensable when the binder properties do not satisfy the speci?cation requirements under hot service temperatures. One of the concerns in using such additives, however, is the increased cost especially for large-sized construction projects. If a natural modi?er can be used to replace some portion of industrial modi?er products, such as SBS, it would signi?cantly help reduce the cost of pavement construction. In this study, Gilsonite, a natural asphalt, is used as a binder modi?er to reduce the SBS content based on a series of rheological testing. While studies on various properties of binder that is modi?ed only by Gilsonite are common, we investigate the effect of combining SBS and Gilsonte in the same base binder. In the ?rst phase, the binders modi?ed individually with SBS and Gilsonite are evaluated in terms of based on the outcomes of dynamic shear rheometer and rotational viscosimeter tests. Then, the asphalt binders including both SBS and Gilsonite at different contents are subjected to the same rheological testing. The results show that around 3–4% times more Gilsonite is needed to replace 1% of SBS when the two modi?ers are mixed in the same binder depending on the Gilsonite/SBS ratio selected. Besides, the viscosity of modi?ed binders with a percent of SBS replaced with Gilsonite is always lower than that of SBS-only modi?ed binder. It is suggested that Gilsonite can be used as an alternative modi?er to reduce the cost of asphalt mixture production and compaction in the ?eld.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: SBS; Gilsonite; Asphalt binder; Rheological properties